Growth of Rice Production in Different Districts of Manipur: a Decadal Analysis - Diana Sarungbam; Nivedita Deka (Journal of Agricultural Extension Management, 2025)
Rice is the most important crop of India and the second most important crop in the world. India accounts for 24.5 per cent of the total production of rice in the world which is the second highest, the highest being China contributing about 36 per cent (Mishra, 2004). In Manipur, a state in north east India, agriculture is the backbone of the state's economy and main source of livelihood of the people with 69 per cent of the workforce depending on agriculture. Rice is the principal food crop of the state and almost 100 per cent of the population depends on rice for their staple food. Therefore, among the agricultural activities, cultivation of rice is the most important activity of the state. The present yield of rice is around 2 tonnes/ha which is quite satisfactory as compared to the all India level. But the actual yield potential of the state is around 4-6 tonnes/ha, which indicates a yield gap. It is important to know the growth in area, production and productivity of rice so as to formulate an appropriate plan for further improving the production and productivity. Therefore, the present study was taken up to analyze the trend of area, production and productivity of rice in different districts of Manipur for the period 1983 to 2003